Photo‐compartmentalized decellularized matrix‐hyaluronan hybrid units for pancreatic tumor‐stroma modeling - Monteiro, Maria V. (2023)
Tissue-derived decellularized extracellular matrix (dECM) provides unique biomolecular cues for bioengineering 3D tumor models with increasingly physiomimetic features. This biomimicry potential can be expanded by combining dECM with key components of native tissues, such as glycosaminoglycans (GAGs). Yet, this combination remains highly challenging, often requiring complex non-natural chemical modifications of dECM biomaterials. Taking advantage of naturally occurring tyrosine moieties, herein a universally applicable methodology is proposed for generating dECM-Hyaluronic acid (HA)-tyramine hydrogels. Enriching dECM with HA, is particularly relevant for modeling tumor-stroma interplay in vitro. By using visible light crosslinking, pancreatic tissue-specific dECM-HA-Tyr tumor-stroma compartmentalyzed platforms are rapidly fabricated on-demand, in superhydrophobic surfaces, while avoiding complex dECM chemical modifications. The generated dECM-HA-Tyr spherically shaped models are able to mimic the desmoplastic stromal environment and are employed for dual screening of pancreatic anti-stromal and anti-tumoral therapeutics. The tumor-stroma models display higher susceptibility to gemcitabine following a first treatment with anti-stroma therapeutics. The developed photo-compartmentalized models ultimately allow to decouple the tumor and stroma compartment, thus enabling the inclusion of other stromal/cancer cells. Moreover, the possibility of combining dECM with virtually any class of tyramine-functionalized macromolecules via on-demand photocrosslinking as herein proposed, extends the use of such hybrid dECM hydrogels.